Research funding and citations in papers of Nobel Laureates in Physics, Chemistry and Medicine, 2019-2020 - Coccia Mario; Roshani Saeed (Journal of Data and Information Science, 2024)
The goal of this study is a comparative analysis of the relation between funding (a main driver for scientific research) and citations in papers of Nobel Laureates in physics, chemistry and medicine over 2019-2020 and the same relation in these research fields as a whole.